Risk management in Iraqi Oil Field Kurdistan Regional Government Case study (Upstream) - Alhiti Kanaan M. Abdlkareem (EDP Sciences, 2021)
The investment decision-maker in oil exploration projects faces overlap in the main criteria, sub-criteria, and attributes of the reasons that control the investment decision, which requires a mechanism that identifies and measures risks in terms of quantity and quality for all alternatives under study. Having a mechanism that deals with such cases will help the decision-maker choose the best alternative by measuring risks and giving the best solution. The main objective of this study is to transfer the uncertainty resulting from the difference in the criteria and features of the problem under investigation into a mechanism that integrates both the Analytical Hierarchy Process (AHP) with the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to choose the optimal solution. The researchers used each (TOPSIS) and APH combined with choosing alternatives by defining criteria, sub-criteria, and oil exploration attributes. Risk management in oil exploration in the Kurdistan region was the subject of this research, which concluded that Erbil blocks' investment is better than the rest of the region. This methodology will act as a guide to help the decision-maker find the best alternative by using both techniques in finding the best investment decision.